Mapping interactions between geology, subsurface resource exploitation and urban development in transforming cities using InSAR Persistent Scatterers: Two decades of change in Florence, Italy. (December 2016) - Pratesi, Fabio; Tapete, Deodato; Del Ventisette, Chiara; Moretti, Sandro
Abstract: Urban expansion and city transformation are increasing reality across the world. Now more than ever it is essential to understand and map at the appropriate scale the processes happening along the verticality and horizontality of cities, to gather robust evidence underpinning strategies for sustainable management of the built environment. This paper explores how established techniques of Persistent Scatterer Interferometry (PSI) can be shaped into a novel dedicated procedure to detect vertical and horizontal urban dynamics including: use and re-use of urban space (new building construction, intentional demolition, renovation projects); exploitation of groundwater resources (induced land subsidence); interactions between new foundations, superficial deposits and bedrock geology (settlement of recent buildings); ground and slope instability affecting settled buildings; susceptibility of heritage assets to structural damages; baseline characterisation prior to planned major infrastructure construction (tunnelling and transportation networks). Florence, central Italy, is used as a demonstration site. This city includes UNESCO World Heritage List historic centre, 20 th -century residential, industrial and peri-urban quarters, and is currently in transition to metropolitan area of over 1 million of inhabitants. Velocity decomposition maps were generated based on millimetre-precise estimates of surface displacements retrieved from PSI processing of the full archives of satellite C-band radar images, including 79 ERS-1/2 descending (1992–2000), 70 ENVISAT ASAR ascending and descending (2003–2010) and 101 RADARSAT-1 ascending and descending (2003–2007). 12 macropatterns and 84 micropatterns in the final map of alert areas highlight a dualism which reflects the physical and urban geography of Florence. North-western and south-western quarters show hot spots of new building construction and regeneration projects for residential, business and tertiary service purposes, alongside issues due to groundwater exploitation and induced land subsidence up to 30–40 mm/yr. Local interactions with underlying geology and natural slope instability processes predominate in the southern and north-eastern sectors. At local scale, stable condition was found for the heritage assets and buildings located along the tracks of the planned subway railway and tramway, with motion rates averagely within ±1.5 mm/yr and localised deformation only up to −3.5 mm/yr. Structural assessment based on future PSI monitoring campaign will benefit of this baseline characterisation. Highlights: We use Persistent Scatterers (PS) to map urban changes and understand dynamics of transforming cities. PS velocity decomposition reveals structural and geologically induced motions. PS location and density are proxies of new buildings, demolitions and regeneration. Pre- and post-2000s changes are mapped across Florence, Italy. Spatial patterns enhance different urban development in W and E parts of Florence.